Professional athletic performance efficiency versus metabolism controlling gene polymorphism and pharmacological support - Buznik, G. V.; Pyatibrat, A. O.; Rodichkin, P. V.; Shabanov, P. D. (Theory and Practice of Physical Culture, 2018)
The study was designed to analyze the bodily homeostasis in extreme situations versus the metabolism controlling gene polymorphism. The study data showed correlations of different gene alleles with adaptability to high physical loads. The effects of Metaprot and Citoflavin on the athletes` functionality indices under extreme physical loads were subject to a pharmacological analysis. Metaprot was found to improve the adaptation mechanisms under extreme loads both at the biochemical and organs-specific levels, with a significant decrease in the working capacity recovery time. Citoflavin was also tested to be of positive effect on the bodily adaptation mechanisms, particularly in rehabilitation periods; with the rehabilitative effects of Citoflavin found most expressed in the athletes tested with different combinations of homozygote alleles associated with the lower aerobic performance indices. The study data and analyses give grounds to conclude that the actual effects of pharmacological agents of nootropic action are largely determined by the anaerobic metabolism controlling gene polymorphism.